Mitochondrial Dysfunction Is an Early Consequence of Partial or Complete Dystrophin Loss in mdx Mice - Moore, Timothy M.; Lin, Amanda J.; Strumwasser, Alexander R.; Cory, Kevin; Whitney, Kate; Ho, Theodore; Ho, Timothy; Lee, Joseph L.; Rucker, Daniel H.; Nguyen, Christina Q.; Yackly, Aidan; Mahata, Sushil K.; et al. (Frontiers in Physiology, 2020)
Duchenne muscular dystrophy (DMD) is characterized by rapid wasting of skeletal muscle. Mitochondrial dysfunction is a well-known pathological feature of DMD. However, whether mitochondrial dysfunction occurs before muscle fiber damage in DMD pathology is not well known. Furthermore, the impact upon heterozygous female mdx carriers (mdx/+), who display dystrophin mosaicism, has received little attention. We hypothesized that dystrophin deletion leads to mitochondrial dysfunction, and that this may occur before myofiber necrosis. As a secondary complication to mitochondrial dysfunction, we also hypothesized metabolic abnormalities prior to the onset of muscle damage. In this study, we detected aberrant mitochondrial morphology, reduced cristae number, and large mitochondrial vacuoles from both male and female mdx mice prior to the onset of muscle damage. Furthermore, we systematically characterized mitochondria during disease progression starting before the onset of muscle damage, noting additional changes in mitochondrial DNA copy number and regulators of mitochondrial size. We further detected mild metabolic and mitochondrial impairments in female mdx carrier mice that were exacerbated with high-fat diet feeding. Lastly, inhibition of the strong autophagic program observed in adolescent mdx male mice via administration of the autophagy inhibitor leupeptin did not improve skeletal muscle pathology. These results are in line with previous data and suggest that before the onset of myofiber necrosis, mitochondrial and metabolic abnormalities are present within the mdx mouse.